Impact of contrast agent injection duration on dynamic contrast‐enhanced MRI quantification in prostate cancer. (5th July 2018) - Klawer, Edzo M.E.; van Houdt, Petra J.; Pos, Floris J.; Heijmink, Stijn W.T.P.J.; van Osch, Matthias J.P.; van der Heide, Uulke A.
Abstract : The volume transfer constant K trans, which describes the leakage of contrast agent (CA) from vasculature into tissue, is the most commonly reported quantitative parameter for dynamic contrast‐enhanced (DCE‐) MRI. However, the variation in reported K trans values between studies from different institutes is large. One of the primary sources of uncertainty is quantification of the arterial input function (AIF). The aim of this study is to determine the influence of the CA injection duration on the AIF and tracer kinetic analysis (TKA) parameters (i.e. K trans, k ep and v e ). Thirty‐one patients with prostate cancer received two DCE‐MRI examinations with an injection duration of 5 s in the first examination and a prolonged injection duration in the second examination, varying between 7.5 s and 30 s. The DCE examination was carried out on a 3.0 T MRI scanner using a transversal T 1 ‐weighted 3D spoiled gradient echo sequence (300 s duration, dynamic scan time of 2.5 s). Data of 29 of the 31 were further analysed. AIFs were determined from the phase signal in the left and right femoral arteries. K trans, k ep and v e were estimated with the standard Tofts model for regions of healthy peripheral zone and tumour tissue. We observed a significantly smaller peak height and increased width in the AIF for injection durations of 15 s and longer. However, we did not find significant differences in K trans, k ep or v e for the studied injection durations. The study demonstrates that the TKA parameters K trans, kep and v e, measured in the prostate, do not show a significant change as a function of injection duration. Abstract : This study investigates the influence of injection duration of contrast agent on the quantification of DCE‐MRI. For longer durations (≥15 s) the peak of the arterial input function became lower and the width was larger. However, no significant difference in tracer kinetic parameter values was found in healthy or tumour prostate tissue.